Pengaruh Pemberian Jus Nanas Dan Madu Terhadap Penyumbuhan Luka Perinum Pada Ibu Post Partum di BPM Ny. Arifin S, SST - Jamila, Fidatul; Anwar, Yuli Yanti (Sekolah Tinggi Ilmu Kesehatan Surabaya, 2017)
In labor there will be injury to the perineum either because of spontaneous tear or episiotomy. In Indonesia, perineal wound is experienced by 75% of mothers giving birth to vaginal. Perineal wound is the rupture of the perineum at the time the fetus is born. Unlike the episiotomy, this tear is traumatic because the perineum is not strong enough to withstand strain when the fetus passes (Siswosudarmo, Ova Emilia, 2012). The purpose of this study is to determine the effect of pineapple juice and honey on perineal wound healing on post partum mothers in BPM Ny. Arifin, SST Surabaya. This research is a pre experimental research with quasi experimental research design. The population in this study were all post partum mothers with a total sample of 32 people divided into two groups, 16 as treatment group and 16 people as control group. The sampling technique is purposive sampling. Data collection using observation sheet and data analysis using chi-square test. The results showed in the treatment group after pineapple and honey juice, most of the perineal wound healed (87.5%). Result of analysis of test of chi-square that is on treatment group p = 0.003 (p<α=0,05). The conclusion of this research is the effect of pineapple and honey juice on perineal wound healing on post partum mother in BPM Ny. Arifin, SST Surabaya. It is expected that post partum mothers to consume foods with balanced nutrition, especially foods that contain lots of protein and vitamins to accelerate the healing of perineal wound.